Conservation liquids on the bases of turbine oil of grade T-30 and corrosion inhibitor (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Conservation liquids have been prepared by adding to T-30 turbine oil different amounts of amidoamine compounds synthesized in 2:1 molar ratio of technical petroleum acids (TPA) to polyethylenepolyamine (PEPA), nitro-compound and phenol-p-alkyl(C8-C12)phenolformaldehyde olygomers on the basis of C14H28 containing Î±-olefin, as well as composition on the bases of them. Defined that the use of these compounds as compositions records high result as corrosion inhibitor in protection of metal constructions.Â